Purslane Weed (Portulaca oleracea): A Prospective Plant Source of Nutrition, Omega-3 Fatty Acid, and Antioxidant Attributes - Md. Kamal Uddin; Abdul Shukor Juraimi; Md Sabir Hossain; Most. Altaf Un Nahar; Md. Eaqub Ali; M. M. Rahman (The Scientific World Journal)
Purslane (Portulaca oleracea L.) is an important plant naturally found as a weed in field crops and lawns. Purslane is widely distributed around the globe and is popular as a potherb in many areas of Europe, Asia, and the Mediterranean region. This plant possesses mucilaginous substances which are of medicinal importance. It is a rich source of potassium (494 mg/100 g) followed by magnesium (68 mg/100 g) and calcium (65 mg/100 g) and possesses the potential to be used as vegetable source of omega-3 fatty acid. It is very good source of alpha-linolenic acid (ALA) and gamma-linolenic acid (LNA, 18 : 3 w3) (4 mg/g fresh weight) of any green leafy vegetable. It contained the highest amount (22.2 mg and 130 mg per 100 g of fresh and dry weight, resp.) of alpha-tocopherol and ascorbic acid (26.6 mg and 506 mg per 100 g of fresh and dry weight, resp.). The oxalate content of purslane leaves was reported as 671–869 mg/100 g fresh weight. The antioxidant content and nutritional value of purslane are important for human consumption. It revealed tremendous nutritional potential and has indicated the potential use of this herb for the future.